2012
DOI: 10.1074/jbc.m111.316836
|View full text |Cite
|
Sign up to set email alerts
|

Structural Link between γ-Aminobutyric Acid Type A (GABAA) Receptor Agonist Binding Site and Inner β-Sheet Governs Channel Activation and Allosteric Drug Modulation

Abstract: Background: Structural elements and protein movements underlying GABA A receptor activation are not completely resolved. Results: Glycine insertions in the extracellular ␤4-␤5 linker decrease GABA activation, invert antagonist efficacy, and reduce allosteric modulation. Conclusion: ␤4-␤5 linker is critical for mediating actions of GABA A receptor orthosteric and allosteric ligands. Significance: Detailed structural-functional understanding of GABA A receptor activation is key to understanding its modulation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…15,16,25 The b3(N110D) subunit mutation lies in the inner b3 sheet, and it seems unlikely that being on the opposite side of the ligand binding channel gating coupling interface would reduce the gating of the channel, but similar results were found after glycine insertions in the inner b4-b5 sheets at the b32 interface with decreased GABA A receptor activation. 26 In line with this, IS-associated mutations mainly affected the kinetic properties of the channel and altered similar domains at the homologous c1/b2 and a1/b2 interfaces required for receptor expression and function. Thus, all 5 de novo GABRB mutations induced a wave of structural -associated b3(D120N, E180G, Y302C) and IS-associated b3(N110D) and b1(F246S) subunit mutations.…”
Section: De Novo B Subunit Mutations Rearrange Conserved Structural Dmentioning
confidence: 74%
See 1 more Smart Citation
“…15,16,25 The b3(N110D) subunit mutation lies in the inner b3 sheet, and it seems unlikely that being on the opposite side of the ligand binding channel gating coupling interface would reduce the gating of the channel, but similar results were found after glycine insertions in the inner b4-b5 sheets at the b32 interface with decreased GABA A receptor activation. 26 In line with this, IS-associated mutations mainly affected the kinetic properties of the channel and altered similar domains at the homologous c1/b2 and a1/b2 interfaces required for receptor expression and function. Thus, all 5 de novo GABRB mutations induced a wave of structural -associated b3(D120N, E180G, Y302C) and IS-associated b3(N110D) and b1(F246S) subunit mutations.…”
Section: De Novo B Subunit Mutations Rearrange Conserved Structural Dmentioning
confidence: 74%
“…The LGS-associated GABRB3 mutations are at the β+/α− interface, which is directly coupled with the ligand binding-channel gating pathway of the receptor 30, 31 . These mutations could be more disruptive to channel function than the IS-associated mutations at the α+/β− and γ+/β− interfaces (that are indirectly coupled by rearrangements throughout the β-sheets/α-helices of the receptor 26 ). For the mutations located in the signal peptide, GABRB3 (P11S, S15F) 6 , and at the γ+/β− interface, GABRB3(G32R) 7 and GABRG2(R82Q, P83S) 32 , the reductions in GABA A receptor currents were smaller (reduced to ~42, ~48, ~50–62, ~34 and ~12% of the wt currents, respectively) than those caused by the LGS-associated GABRB3(D120N, E180G, Y302C) mutations (reduced to ~24, ~1, ~5% of the wt currents, respectively) located at the β+/α− interface.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified that β‐subunit is a key subunit in the potentiation of GABA A receptor by pentobarbital . Similarly, we estimated the possible binding site of NMZM on GABA A receptor and whether potentiation of GABA A receptor by NMZM was influenced by pentobarbital.…”
Section: Resultsmentioning
confidence: 97%
“…In particular, GABA‐ARs with a gamma 2 subunit are synaptic (Nusser et al ., ) and necessary for benzodiazepine sensitivity (Pritchett et al ., ; Saxena and Macdonald, ). Benzodiazepines bind at the pocket between alpha and gamma subunits (Nusser et al ., ; Venkatachalan and Czajkowski, ), while barbiturates and propofol bind the beta subunit that is ubiquitous for all GABA‐ARs (Amin and Weiss, ; Serafini et al ., ). Therefore, the movement of gamma 2 subunit‐containing GABA‐ARs away from synapses by lateral diffusion (Bannai et al ., ; Muir et al ., ) and/or receptor trafficking (Naylor et al ., ; Terunuma et al ., ) would preferentially affect the receptors with the greatest benzodiazepine sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Immunocytochemical labelling of the gamma 2 subunit, used to synaptically locate GABA‐ARs (Nusser et al ., ) and associated with the synaptic clustering molecule gephyrin (Essrich et al ., ), confirms the decrease in the expression of synaptic receptors predicted by physiological measurements (Naylor et al ., ). The gamma 2 subunit also confers benzodiazepine sensitivity of synaptic GABA‐ARs (Saxena and Macdonald, ); benzodiazepines bind at the pocket between alpha and gamma 2 subunits (Nusser et al ., ; Venkatachalan and Czajkowski, ), and gamma 2 is essential for benzodiazepine sensitivity (Pritchett et al ., ; Sigel et al ., ). Consequently, the loss of synaptic gamma2 subunit‐containing GABA‐ARs would be expected to decrease the number of available receptors for benzodiazepine binding and action.…”
Section: Seizure‐induced Trafficking Of Gaba‐ars With Loss Of Synaptimentioning
confidence: 99%